Clinical value and survival analysis of subcutaneous soft tissue metastasis detected by 18F-FDG PET/CT - Yufei Gao; Hui Zhang; Tiancheng Hao; Lizhuo Jia; Jiangmeng Wu; Dongxue Wu; Siqi Wu; Yong Wang (Frontiers in Oncology)
ObjectiveTo retrospectively analyze cases of whole-body 18F-FDG PET/CT imaging, identify abnormal images of subcutaneous nodules, and explore the clinical application value of PET/CT in detecting subcutaneous soft tissue metastases and its impact on survival.MethodAn analysis was conducted on cases from August 2019 to August 2024, and 57 cases of subcutaneous nodules were found to have positive 18F-FDG imaging, all of which underwent pathological puncture or biopsy. Collect patient histological subtypes, metastasis patterns, treatment, and survival rates. Kaplan Meier curves were used to estimate survival time, and Mantel-Cox univariate analysis was used to determine the correlation between extensive metastasis, degree of soft tissue involvement, systemic and local treatment, and survival time.ResultAmong the 57 patients confirmed by pathology, 10 were benign and 47 were malignant. Among 47 cases of malignant tumors, 39 cases were postoperative cases, 8 cases were preoperative cases, and 4 cases had unknown primary lesions. A total of 88 subcutaneous lesions were found, including 28 patients with a single lesion, 12 patients with two lesions, and 8 patients with three or more lesions. One patient with unknown primary lesion reported abdominal wall nodules as the main symptom. PET/CT assisted in qualitative localization in 11 cases. Univariate analysis showed that the median survival time (22 months) of patients who did not receive local radiotherapy was significantly shorter than that of patients who did receive local radiotherapy (60 months) (P<0.05). There is no correlation between gender, metastasis pattern, metastasis at initial diagnosis, use of chemotherapy, and survival time.ConclusionWhole body PET/CT imaging has important application value in the diagnosis of subcutaneous soft tissue metastasis. By comprehensively evaluating the patient’s overall condition and accurately determining whether there is a simple soft tissue metastasis, local intervention measures can bring more favorable prognosis for patients with good general condition and only soft tissue metastasis.